(untitled) (Canadian Journal of Native Studies, 2026)
Recently, there has been a political movement by Indigenous peoples and their allies to decolonize and Indigenize the academy. But often times, so-called allies can do more harm in their attempts to achieve justice and equality for others because they lack the appropriate knowledge and understandings of those whom they aim to aid. One key question that people who are interested in justice for Indigenous peoples should ask is what it means to “Indigenize” something. My goal here is to explore what it means to ‘Indigenize’ Philosophy by questioning who can do so, to what extent, and what is required.